Leader-Following Consensus of Discrete-Time Multiagent Systems With Encoding-Decoding - Li, Huaqing; Chen, Guo; Liao, Xiaofeng; Huang, Tingwen (IEEE transactions on circuits and systems. II, Express briefs, 2016)
The leader-following consensus of general linear discrete-time multiagent systems with a limited communication data rate and a directed fixed topology is investigated. The consensus protocol is designed for each agent, which is given in terms of states of its encoder and decoders with time-varying quantization levels. A rigorous analysis for the consensus convergence is provided. A finite lower bound of the communication data rate between each pair of adjacent agents is obtained to ensure consensus. A numerical example is presented to demonstrate the validity of the results obtained.